PENGEMBANGAN LKPD MATEMATIKA BERBASIS PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA PADA MATERI PECAHAN KELAS IV SD - Tria Nur Maulida; Muhammad Febri Rafli; Mahlianurrahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Deep mastery of mathematical concepts serves as a critical foundation for students to solve various mathematical problems. However, empirical evidence at SD Negeri Tanah Merah indicates that the majority of fourth-grade studentsspecifically 12 out of 16 students (75%) have not achieved the Minimum Competency Criteria (KKTP) in fraction topics. This issue stems from the reliance on conventional instructional materials, where student worksheets predominantly feature brief summaries and mechanical drills without guiding structured reasoning. This study aims to develop, validate, evaluate the practicality, and analyze the effectiveness of a Problem Solving-based Student Worksheet (LKPD) focused on equivalent fractions. Applying a Research and Development (R&D) approach guided by the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study involved 16 fourth-grade students. Data collection instruments comprised expert validation sheets, teacher and student feedback questionnaires, and mathematical comprehension tests (pretest and posttest). Quantitative descriptive analysis revealed that the developed LKPD achieved a validity score of 98.67% (highly valid), with practicality ratings of 97.5% from the teacher and 96.09% from students (highly practical). Furthermore, the effectiveness evaluation yielded an average N-Gain score of 0.85, classified in the high category. These findings demonstrate that the Problem Solving-based LKPD is highly effective and suitable as an innovative learning tool to enhance elementary students' mathematical understanding of equivalent fractions.